Synergistic effect of serine protease inhibitors and a bothropic antivenom in reducing local hemorrhage and coagulopathy caused by Bothrops jararaca venom. (August 2021) - Silva, G.M.; Berto, D.H.; Lima, C.A.; Waitman, K.B.; Lima, C.F.G.; Prezoto, B.C.; Vieira, M.L.; Rocha, M.M.T.; Gonçalves, L.R.C.; Andrade, S.A.
Abstract: Snakebite accidents are a public health problem that affects the whole world, causing thousands of deaths and amputations each year. In Brazil, snakebite envenomations are caused mostly by snakes from the Bothrops genus. The local symptoms are characterized by pain, swelling, ecchymosis, and hemorrhages. Systemic disturbances can lead to necrosis and amputations. The present treatment consists of intravenous administration of bothropic antivenom, which is capable of reversing most of the systemic symptoms, while presenting limitations to treat the local effects, such as hemorrhage and to neutralize the snake venom serine protease (SVSP). In this context, we aimed to evaluate the activity of selective serine protease inhibitors (pepC and pepB) in combination with the bothropic antivenom in vivo . Further, we assessed their possible synergistic effect in the treatment of coagulopathy and hemorrhage induced by Bothrops jararaca venom. For this, we evaluated the in vivo activity in mouse models of local hemorrhage and a series of in vitro hemostasis assays. Our results showed that pepC and pepB, when combinated with the antivenom, increase its protective activity in vivo and decrease the hemostatic disturbances in vitro with high selectivity, possibly by inhibiting botropic proteases. These data suggest that the addition of serine protease inhibitor to the antivenom can improve its overall potential. Graphical abstract: Image 1 Highlights: Peptides inhibitors associated with bothropic antivenom improve the neutralization of local hemorrhage. Fibrinogen consumption and coagulopathy decreased using bothropic antivenom associated to selective peptides inhibitors. Venom serine protease inhibitors do not affect the human coagulation cascade.